Cyclosporine A in Ullrich Congenital Muscular Dystrophy: Long-Term Results. (17th October 2011) - Merlini, Luciano; Sabatelli, Patrizia; Armaroli, Annarita; Gnudi, Saverio; Angelin, Alessia; Grumati, Paolo; Michelini, Maria Elena; Franchella, Andrea; Gualandi, Francesca; Bertini, Enrico; Maraldi, Nadir Mario; Ferlini, Alessandra; et al.
Abstract : Six individuals with Ullrich congenital muscular dystrophy (UCMD) and mutations in the genes-encoding collagen VI, aging 5–9, received 3–5 mg/kg of cyclosporine A (CsA) daily for 1 to 3.2 years. The primary outcome measure was the muscle strength evaluated with a myometer and expressed as megalimbs. The megalimbs score showed significant improvement (P = 0.01 ) in 5 of the 6 patients. Motor function did not change. Respiratory function deteriorated in all. CsA treatment corrected mitochondrial dysfunction, increased muscle regeneration, and decreased the number of apoptotic nuclei. Results from this study demonstrate that long-term treatment with CsA ameliorates performance in the limbs, but not in the respiratory muscles of UCMD patients, and that it is well tolerated. These results suggest considering a trial of CsA or nonimmunosuppressive cyclosporins, that retains the PTP-desensitizing properties of CsA, as early as possible in UCMD patients when diaphragm is less compromised.